The Influence of Cinema Screen Colors on The Heart Rate and Blood Pressure among Students in the College of Fine Arts - Hameed Rasheed, Rajaa (Diyala Journal of Medicine, 2020)
Background: The strong relationship between hypertension and stress have been confirmed in previous studies. The stress has been shown in rise blood pressure by rising heart rate and the cardiac output . Objective: To test the influences of exposure to red versus green light colors of cinema screen on the rate of heart beat and blood pressure among healthy college students. Patients and Methods: In this study a twenty eight apparently healthy students from college of fine arts Diyala University were enrolled. They were 18 males and 10 females with a mean age 22 years. Verbal consent was obtained from all participants. They were exposed to two colored lights of cinema screen (red and green) viewing at a distance 4 meters. The watching time was continued for 15 minutes. Thereafter ten minutes the systolic blood pressure [SBP], diastolic blood pressure [DBP] and heart rate was measured by medical personals. Data were collected and statistical analysis was done using the SPSS version 20 and P value was counted significant whenever it is less than 0.05. Results: The results revealed that the exposure to red light increases both systolic and diastolic blood pressure and heart rate compared to the green light, since the mean ±SD of diastolic blood pressure for red light and green light are 8.22±0.59 and 8.02±0.66 versus that of the control is 7.81±0.46 cmHg. Thus Red and green light had a significant effect on diastolic blood pressure (P <0.05). Whereas, the mean ± SD of systolic blood pressure for red light and green light are 11.85±1.11 and 11.77±1.24 versus that of the control (11.75±0.96) cmHg, with insignificant difference (P > 0.05). The mean ±SD of heart rate for red light and green light are 79.75±11.19 and 79.10±9.87versus that of the control 76.71±8.81 beats/min. Conclusion: Exposure to red and green cinema screen colors is altering autonomic nervous functions as expressed by increasing the blood pressure and heart rate among healthy college students.